2022
DOI: 10.3389/fendo.2022.815999
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Study of Colorectal Cancer Caused by Altered Gut Microbiota After Cholecystectomy

Abstract: Epidemiological studies have found an increased incidence of colorectal cancer (CRC) in people who undergo cholecystectomy compared to healthy individuals. After cholecystectomy, bile enters the duodenum directly, unregulated by the timing of meals. Disruption of the balance of bile acid metabolism and increased production of primary bile acids, which in turn affects the composition and abundance of intestinal microorganisms. The link among cholecystectomy, the gut microbiota, and the occurrence and developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 100 publications
(134 reference statements)
1
8
0
Order By: Relevance
“…Until now, it is widely shown that PC patients have a higher risk of gastrointestinal complications, but no increased risk of IBD in PC patients has been reported in limited studies, and the mechanism was also not clearly underlined in animals. 4 , 5 In our present time-course study, we have shown that cholecystectomy, after a relatively longer duration of post-operation, ameliorated DSS-induced colitis in mice, in keeping with our published research suggested that the follow-up period was a pivotal factor for clinical outcomes in PC patients. 17 Based on decades-long duration in the PC patients, further studies are needed a markedly long follow-up year to clarify the role of duration after cholecystectomy in IBD patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Until now, it is widely shown that PC patients have a higher risk of gastrointestinal complications, but no increased risk of IBD in PC patients has been reported in limited studies, and the mechanism was also not clearly underlined in animals. 4 , 5 In our present time-course study, we have shown that cholecystectomy, after a relatively longer duration of post-operation, ameliorated DSS-induced colitis in mice, in keeping with our published research suggested that the follow-up period was a pivotal factor for clinical outcomes in PC patients. 17 Based on decades-long duration in the PC patients, further studies are needed a markedly long follow-up year to clarify the role of duration after cholecystectomy in IBD patients.…”
Section: Discussionsupporting
confidence: 91%
“… 2 , 3 Cholecystectomy also induced intestinal bacterial and bile acids dysbiosis. 4 , 5 Even so, few studies reported the association between cholecystectomy and IBD. In a population-based cohort study, the risk of IBD did not change significantly between the PC patients and healthy controls (0.062% vs 0.051%).…”
Section: Introductionmentioning
confidence: 99%
“…And its impact on health is still unclear. Deoxycholic acid (DCA) and some pathogenic bacteria are considered to be tumorigenic [12,22]. Previous study has suggested that secondary bile acids concentration were higher in the right colon [23] and an increased rate of right CRC after cholecystectomy was also observed [4,9,20].…”
Section: Discussionmentioning
confidence: 99%
“…In individuals who have undergone cholecystectomy (CC), there is evidence of increased production of secondary BAs, a phenomenon documented in both experimental and clinical studies [ 11 , 23 ]. Additionally, with specific reference to deoxycholic acid (DCA), an increased incidence of certain types of cancer has been observed in patients who have undergone cholecystectomy [ 24 ]. It has been suggested that DCA possesses carcinogenic and mutagenic properties, and there is also evidence indicating that DCA itself can contribute to gut dysbiosis [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%